Collaborative Reasoning With Strategy Instruction for Opinion Writing in Primary Grades: Two Cycles of Design Research - Traga Philippakos, Zoi A.; MacArthur, Charles A.; Munsell, Sarah (Reading & writing quarterly, 2018)
Argumentation is challenging for young learners. We used design research to develop an intervention that was based on principles of dialogic argumentation and strategy instruction and used genre elements to guide planning and evaluation for revision. Instruction included oral discussion of children's books, written responses to reading, and the writing of argumentative essays. We based professional development (PD) on the principles of practice-based PD. The study included 2 cycles of design research with implementation of PD and the instructional approach. Cycle 1 included kindergarten and 1st grade (7 weeks, 168 students, 10 teachers); Cycle 2 included kindergarten, 1st grade, and 2nd grade (5 weeks, 229 students, 12 teachers). We made improvements to instruction and PD between cycles based on the design research. Pretest-posttest comparisons showed improvements in quality in both cycles and more genre elements in Cycle 2. Teachers responded positively to PD. We discuss limitations and implications for future research.